Hydride generation-flame atomic absorption spectrometric quantification of trace lead after the extraction by fatty acid functionalized Fe3O4 nanoparticles assisted dispersive solid-phase extraction: a sensitive, precise and accurate analytical method - Akkaya, Erhan; Ozturk, Elif; Kasa, Nursu Aylin; Cetin, Gulten; Komesli, Okan Tarik; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2020)
This study presents a dispersive solid-phase extraction (DSPE) method based on fatty acid (stearic acid) functionalized magnetite nanoparticles (SACMNP) for the extraction and preconcentration of ultra-trace lead from aqueous samples for sensitive determination by a hydride generation-flame atomic absorption spectrometry (HG-FAAS) system. To achieve that, magnetite nanoparticles (MNPs) were synthesized and coated with stearic acid in order to obtain a higher surface area and increased selectivity. The optimum values obtained from the combination of HG-FAAS and SACMNP-DSPE were determined through the one-variable-at-a-time optimization technique. The following results were calculated under the optimum conditions; a limit of detection (LOD) value of 0.16 mu g L-1 and a limit of quantification (LOQ) value of 0.52 mu g L-1. Standard and certified reference materials (SRM and CRM) were used to verify the developed method's accuracy and the results obtained (SRM: 99.6 +/- 5.8%, CRM: 101.8 +/- 4.9%) indicated high quantification accuracy.
Keywords: LIQUID-LIQUID MICROEXTRACTION; CARBON NANOTUBES; WATER SAMPLES; CADMIUM; PRECONCENTRATION; COPPER; PB; PLASMA; IONS; CD; Chemistry; Spectroscopy